# Prove that n.1 + (n-1).2 + (n-2).3 . 3.(n-2) + 2.(n-1) + 1.n = n(n+1)(n+2)/6 By

1. Jul 17, 2011

### Arnab Chattar

Prove that n.1 + (n-1).2 + (n-2).3 ....... 3.(n-2) + 2.(n-1) + 1.n = n(n+1)(n+2)/6 By

You cant put n=1 in the L.H.S, when we take p(1) it means the first term i.e. 'n.1' and in the R.H.S n=1 should be put that means p(1) : n.1=1 which is wrong...now can you answer it...plz solve it??

2. Jul 17, 2011

### tiny-tim

Welcome to PF!

HI Arnab! Welcome to PF!
Yes we can …

the LHS has n terms, so if n = 1, that's 1 term, and the LHS is 1
.1 = 1 (and the RHS is 1.2.3/6 = 1 also).

3. Jul 17, 2011

### math4math

Re: Prove that n.1 + (n-1).2 + (n-2).3 ....... 3.(n-2) + 2.(n-1) + 1.n = n(n+1)(n+2)/

Yes, by plugging in n=1, we consider the first term only on LHS and that is = 1
Also substituting n = 1 on RHS, we get 1
Hence, nothing wrong when n=1

4. Jul 19, 2011

### Delusional

Re: Prove that n.1 + (n-1).2 + (n-2).3 ....... 3.(n-2) + 2.(n-1) + 1.n = n(n+1)(n+2)/

\begin{aligned}\sum_{k=1}^{n} (n-k+1)k = (n+1)\sum_{k=1}^{n}k-\sum_{k=1}^{n}k^2= (n+1)\left[ \frac{1}{2} n (n+1)\right]-\frac{1}{6}n (n+1) (2 n+1) = \frac{1}{6}n (n+1) (n+2).\end{aligned}